Perbedaan Kadar Hepsidin pada Remaja Putri Anemia dan Non Anemia - Pasalina, Putri Engla; Sari, Nirmala; Devita, Hendri (LPPM Hang Tuah Pekanbaru, 2024)
Anemia affects 32% of Indonesian teenagers, which means that 3–4 out of 10 of them have the condition. Adolescent anemia will develop into pregnant anemia if it is not treated, which will affect the results for the mother and the newborn and could raise the chance of stunting. Before iron is distributed and stored as reserves (ferritin), hepcidin is a crucial hormone that controls systemic iron homeostasis. A test of hepcidin can distinguish between iron deficiency anemia and anemia of chronic disease. The purpose of this study is to examine the variations in hepcidin levels between teenage girls who are anemic and those who are not. This study uses a cross-sectional comparative approach and is of the observational analytical kind. Female students in their late teens attending Baiturrahmah University in Padang made up the study's sample. Requirements for inclusion include not having a history of diabetes mellitus, kidney illness, hemoglobinopathy, or smoking. Using a sequential sampling procedure, 36 individuals were selected, 18 of whom had anemia and the remaining 18 of whom did not. Hepcidin levels are derived from the outcomes of the ELISA method used to measure the serum hepcidin-25. The statistical test used is the Mann-Whitney test because the data is not normally distributed. The results showed that the average hepcidin level in the anemia group was lower than the hepcidin level in the non-anemia group (0,43±0,1 ng/ml vs 0,46±0,09 ng/ml. Statistical tests showed that there was no significant difference between hepcidin levels in the anemia group and the non-anemia group (p=0,43). The conclusion was that there was no significant relationship between hepcidin levels and anemia in adolescents. It is recommended that further research be conducted on hepcidin and other biomarkers that affect the action of hepcidin and the need to consider hepcidin testing in diagnosing anemia.